DAMPAK BADAN USAHA MILIK DESA (BUMDES) TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA TUTUR - Khumaidi Khumaidi; Siti Zaynab (Journal Publicuho, 2021)
Badan Usaha Milik Desa thereafter called BUMDes is an alternative to improve the rural economy. Unfortunately, however, the position of BUMDes had not been governed completely in existing legislation. Another more complex problem is that in choosing an appropriate enterprise for establishing BUMDes. This study aims to describe the impact of BUMDES on the welfare of rural communities. BUMDES is one of the programs to strengthen the role of the region.This research was conducted using a qualitative approach and used in-depth interview and observation techniques. The results of the study have shown that BUMDES has had an impact on the village economy. BUMDES has an impact on community business development in Tutur Village. In addition, BUMDES encourages people to start a new business according to the potential of the community. The impact of other BUMDES is to improve the level of children's education and improve public health